CONSTRUCTION OF WATER ROCKET GAME PROPS FOR SCIENCE LEARNING IN PRIMARY SCHOOLS - Fatimah, Siti; Widodo, Rudi Danang; Rahman, Rifqi Aulia; Lana, Syifa' (JPI (Jurnal Pendidikan Indonesia), 2018)
A water rocket is one of the simple types of props that comprise many science concepts. Manufacturing the water rocket is simple but every movement of water rocket launch needs high analysis. This research aims to design a scheme of water rocket props and to analyze the factors that affect the furthest distance of the water rocket launch. Some science concepts in the water rocket launch are examined. The results represent that throwing at 45-degree angle produces the furthest distance. The shape of the water rocket's propeller is a trapezoid with a total of 3 propellers. The results also can be used as a reference material for teachers in conveying science knowledge so the learning science will be more concrete and fun, especially in primary school.